A revision of the water beetle genus Hydraena Kugelann for southern Africa (Coleoptera: Hydraenidae) - Perkins, Philip D. (Zootaxa, 2014)
The southern African species of the water beetle genus Hydraena Kugelann, 1794, are revised. Twenty-eight new species are described, and redescriptions and new collection records are given for three previously described species, based on the examination and databasing of 11,534 specimens from 488 localities/events. Male genitalia are illustrated, and high resolution habitus images of the holotypes are provided. Distribution maps are given for the 31 species of Hydraena now known from southern Africa, including Namibia, South Africa, Lesotho, Botswana, Zimbabwe, and the extreme southern part of Angola. New species of Hydraena are: H. armatura (Zimbabwe: Tributary stream of the Mutoragundu River); H. biseptosa (South Africa: Mpumalanga Province, Soutpansberg, Entabeni); H. capensis (South Africa: Eastern Cape Province, Chapman’s Bay); H. caprivica (Namibia: East Caprivi: Katima Mulilo); H. clavicula (South Africa: Mpumalanga Province, Uitsuk); H. cooperoides (Namibia: Naukluft River); H. duodecimata (South Africa: Northern Cape Province, Richtersveld, Oemsberg); H. elephanta (Angola: Altoplano, Ongueria); H. favulosa (Zimbabwe: Matapos National Park); H. genumorpha (South Africa: KwaZulu-Natal Province, Karkloof Grassveld); H. habitiva (South Africa: Mpumalanga Province, Nelshoogte); H. humanica (South Africa: Mpumalanga Province, Blyderiver Canyon); H. injectiva (South Africa: Mpumalanga Province, Nelshoogte); H. mpumalanga (South Africa: Mpumalanga Province, Soutpansberg, Entabeni); H. multimurata (South Africa: Mpumalanga Province, Kruger Nat. Pk., Letaba River); H. namibiensis (Namibia: C. Namib desert, Numis Wasser); H. natiforma (South Africa: Free State Province, Kruger Nat’l Park, Pretariuskop); H. neoaccurata (South Africa: Mpumalanga Province, Nelshoogte); H. nomenipes (South Africa: Eastern Cape Province, S. coast, Dwesa forest reserve); H. pisciforma (South Africa: Mpumalanga Province, Kruger National Park, Skukuza, Sabie River); H. profunda (South Africa: Mpumalanga Province, God’s Window); H. reflectiva (South Africa: Eastern Cape Province, S. coast, Dwesa forest reserve); H. sebastiani (South Africa: Western Cape Province, Groot Toren farm); H. tiara (South Africa: Mpumalanga Province, Vaal River where crossed by Ermelo-Lake Chrissie Road); H. uniforma (Namibia: Brandberg, Wasserfallflache); H. vadosa (South Africa: Eastern Cape Province, Amatole, Pirie Forest); H. zimbabwensis (Zimbabwe: Matapos National Park).